A case report of distal radial puncture in a patient with acute upper limb ischaemia: the last hope of the cardiologist?. Issue 7 (24th May 2022) - Giusca, Sorin; Schmidt, Andrej; Korosoglou, Grigorios
Abstract: Background: Patients with acute limb ischaemia (ALI) present with acute symptoms, requiring prompt diagnosis and expedited treatment to preserve the viability of the affected ischaemic tissue. Case summary: We present an 83-year-old female patient with upper ALI due to thrombotic occlusion of the left brachial artery. Concomitantly, the patient had a first diagnosis of atrial fibrillation and was not on treatment with oral anticoagulation. Transfemoral thrombectomy using a 6F Rotarex® catheter resulted in removal of the thrombus from the brachial artery. However, significant amounts of debris embolized distally, causing occlusion of both the radial and ulnar arteries. The debris was successfully removed after puncture of the distal radial artery and retrograde thrombus aspiration using a 5F Envoy catheter. This manoeuver led to flow restoration in both the radial and ulnar arteries and to complete resolution of ischaemic symptoms of the patient. Discussion: Interventionists may consider distal radial puncture not only as an access site for coronary angiography but also as an option for the endovascular management of ALI in cases of cardiac embolism, as described herein or in cases of thrombotic complications during routine catheterization and percutaneous coronary intervention . Herein, we describe the case of an 83-year-old patient, who presented with acute upper limb ischaemia. Due to embolization of thrombotic debris during Rotarex® catheter thrombectomy, flow further diminished in the ulnar and radial arteries. The last hope for successful interventional treatment was thrombectomy from distally after retrograde puncture of the distal radial artery. This unique manoeuver led to flow restoration and complete recovery of the patient without the need for open surgery.